Twelve Days at Nuku Hiva : Russian Encounters and Mutiny in the South Pacific - Govor, Elena (Book collections on Project MUSE., 2010)
In August 1803 two Russian ships, the Nadezhda and the Neva, set off on a round-the-world voyage to carry out scientific exploration and collect artifacts for Alexander I's ethnographic museum in St. Petersburg. Russia's strategic concerns in the north Pacific, however, led the Russian government to include as part of the expedition an embassy to Japan, headed by statesman Nikolai Rezanov, who was given authority over the ships' commanders without their knowledge. Between them the ships carried an ethnically and socially disparate group of men: Russian educated elite, German naturalists, Siberian merchants, Baltic naval officers, even Japanese passengers. Upon reaching Nuku Hiva in the Marquesas archipelago on May 7, 1804, and for the next twelve days, the naval officers revolted against Rezanov's command while complex crosscultural encounters between Russians and islanders occurred. Elena Govor recounts the voyage, reconstructing and exploring in depth the tumultuous events of the Russians' stay in Nuku Hiva; the course of the mutiny, its resolution and aftermath; and the extent and nature of the contact between Nuku Hivans and Russians. Govor draws directly on the writings of the participants themselves, many of whom left accounts of the voyage. Those by the ships' captains, Krusenstern and Lisiansky, and the naturalist George Langsdorff are well known, but here for the first time, their writings are juxtaposed with recently discovered textual and visual evidence by various members of the expedition in Russian, German, Japanese--and by the Nuku Hivans themselves. Two sailor-beachcombers, a Frenchman and an Englishman who acted as guides and interpreters, later contributed their own accounts, which feature the words and opinions of islanders. Govor also relies on a myth about the Russian visit recounted by Nuku Hivans to this day. With its unique polyphonic historical approach, Twelve Days at Nuku Hiva presents an innovative crosscultural ethnohistory that uncovers new approaches to--and understandings of--what took place on Nuku Hiva more than two hundred years ago.